Proceedings of SPE Latin American and Caribbean Petroleum Engineering Conference 2001
DOI: 10.2523/69561-ms
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Numerical Simulation of an Extra-Heavy Crude Oil Downhole Upgrading Process Using Hydrogen Donors Under Cyclic Steam Injection Conditions

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractPhysical simulation experiments of a Downhole Upgrading Process showed that use of a hydrogen donor additive (tetralin) in the presence of methane (natural gas) and the mineral formation under steam injection conditions (280°C and residence times greater than 24 h) led to an increase of at least three degree in API gravity of the treated Extra-Heavy Crude Oil, three-fold viscosity reduction and, approximately, 8% decrease in the asphaltene content with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It can be found that after the reaction, yield of low boiling point fraction changes a little, but that of high boiling point fraction decreases significantly. This is because during the aquathermolysis reaction, heavy component in heavy oil translates into light component due to breakage of carbon bonds and hydrogen ion joining. , Oxidative decomposition reaction occurs with the existence of water and O 2 in no. 3.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It can be found that after the reaction, yield of low boiling point fraction changes a little, but that of high boiling point fraction decreases significantly. This is because during the aquathermolysis reaction, heavy component in heavy oil translates into light component due to breakage of carbon bonds and hydrogen ion joining. , Oxidative decomposition reaction occurs with the existence of water and O 2 in no. 3.…”
Section: Results and Discussionmentioning
confidence: 99%